Adeno-Associated Virus Activates an Innate Immune Response in Normal Human Cells but Not in Osteosarcoma Cells - Laredj, Leila N. (American Society for Microbiology, 2011)

(untitled)
Adeno-associated virus (AAV) is a small, DNA-containing dependovirus with promising potential as a gene delivery vehicle. Given the variety of applications of AAV-based vectors in the treatment of genetic disorders, numerous studies have focused on the immunogenicity of recombinant AAV. In general, AAV vectors appear not to induce strong inflammatory responses. We have found that AAV2, when it infects the osteosarcoma cells U2OS, can initiate part of its replicative cycle in the absence of helper virus. This does not occur in untransformed cells. We set out to test whether the cellular innate antiviral defenses control this susceptibility and found that, in nonimmune normal human fibroblasts, AAV2 induces type I interferon production and release and the accumulation of nuclear promyelocytic leukemia bodies. AAV fails to mobilize this defense pathway in the U2OS cells. This permissiveness is in large part due to impairment of the viral sensing machinery in these cells. Our investigations point to Toll-like receptor 9 as a potential intracellular sensor that detects AAV2 and triggers the antiviral state in AAV-infected untransformed cells. Efficient sensing of the AAV genome and the ensuing activation of an innate antiviral response are thus crucial cellular events dictating the parvovirus infectivity in host cells.